WinCuts: Manipulating Arbitrary Window Regions for More Effective Use of Screen Space - Tan, Desney; Meyers, Brian; Czerwinski, Mary (Extended Abstracts of Proceedings of ACM Human Factors in Computing Systems CHI 2004, 2004)
Each window on our computer desktop provides a view into some information. Although users can currently manipulate multiple windows, we assert that being able to spatially arrange smaller regions of these windows could help users perform certain tasks more efficiently. In this paper, we describe a novel interaction technique that allows users to replicate arbitrary regions of existing windows into independent windows called WinCuts. Each WinCut is a live view of a region of the source window with which users can interact. We also present an extension that allows users to share WinCuts across multiple devices. Next, we classify the set of tasks for which WinCuts may be useful, both in single as well as multiple device scenarios. We present high level implementation details so that other researchers can replicate this work. And finally, we discuss future work that we will pursue in extending these ideas.